FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK KEPATUHAN PEKERJA TERHADAP PROCESS SAFETY INFORMATION (PSI) DI AREA X PT. Y - Dean Yustisia Putra; Yuliani Setyaningsih; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Process Safety Information (PSI) contains technical information needed to identify hazards, assessing risk potentials, and maintaining the risk itself to actualize a safety operation. Area X is a Gathering Station which serves as a collecting place for drilling fluids such as oil, water and gas from oil wells. Results from observatuon and interviews shows that 20,2% workers at Area X have a low level of knowledge and understanding of PSI. Factors correlating with workers’ obedience such as age, knowledge, manner, motivation, social support, and Safety Talk. The study is conducted in quantitative design with cross-sectional approach. The population are 60 workers of Area X. The sampling method uses purposive samping formula and results in 37 subjects. Data collecting conducted by inquiries filled by the subjects. Results of statistical test using chi-square, the correlating factors are manner (p-value=0,032), motivation (p-value=0,011), while toe non-correlating factors are age (p-value=0,493), knowledge (p-value=0,866), social support (p-value=0,417), and Safety Talk/Toolbox Meeting (p-value=0,183). The management are suggested to educate the workers by media such as by e-mail, an for Team Leaders in Area X to assist the workers to understand the PSI.